Structure and Temporal Dynamics of Populations within Wheat Streak Mosaic Virus Isolates - Hall, Jeffrey S. (American Society for Microbiology, 2001)
Variation within the Type and Sidney 81 strains of wheat streak mosaic virus was assessed by single-strand conformation polymorphism (SSCP) analysis and confirmed by nucleotide sequencing. Limiting-dilution subisolates (LDSIs) of each strain were evaluated for polymorphism in the P1, P3, NIa, and CP cistrons. Different SSCP patterns among LDSIs of a strain were associated with single-nucleotide substitutions. Sidney 81 LDSI-S10 was used as founding inoculum to establish three lineages each in wheat, corn, and barley. The P1, HC-Pro, P3, CI, NIa, NIb, and CP cistrons of LDSI-S10 and each lineage at passages 1, 3, 6, and 9 were evaluated for polymorphism. By passage 9, each lineage differed in consensus sequence from LDSI-S10. The majority of substitutions occurred within NIa and CP, although at least one change occurred in each cistron except HC-Pro and P3. Most consensus sequence changes among lineages were independent, with substitutions accumulating over time. However, LDSI-S10 bore a variant nucleotide (G(6016)) in NIa that was restored to A(6016) in eight of nine lineages by passage 6. This near-global reversion is most easily explained by selection. Examination of nonconsensus variation revealed a pool of unique substitutions (singletons) that remained constant in frequency during passage, regardless of the host species examined. These results suggest that mutations arising by viral polymerase error are generated at a constant rate but that most newly generated mutants are sequestered in virions and do not serve as replication templates. Thus, a substantial fraction of variation generated is static and has yet to be tested for relative fitness. In contrast, nonsingleton variation increased upon passage, suggesting that some mutants do serve as replication templates and may become established in a population. Replicated mutants may or may not rise to prominence to become the consensus sequence in a lineage, with the fate of any particular mutant subject to selection and stochastic processes such as genetic drift and population growth factors.